Morphological intraspecific variability of some Thymus vulgaris L. varieties in connection with their productivity - H.A.H. AL-Qaarawi; E. L. Malankina; L. N. Kozlovskaya (Овощи России, 2020)
Relevance. Common thyme or garden thyme Thymus vulgaris L. (Lamiaceae L.) is the medicinal and aromatic plant containing essential oil which is the source of thymol and other phenol derivatives. This species is characterized by significant morphological and chemical polymorphism. Thymus vulgaris L. has numerous varieties and subspecies which are complicates for the identification of raw materials and makes its quality unstable. The study of intraspecific variability, not only by phenotype but also by biochemical parameters, is an urgent task in the search for varieties and samples of Thýmus vulgáris L. that are promising for the medical industry.Materials and methods. The research material was obtained from botanical institutions and firms in Russia, the Czech Republic and Germany and introduced on the experimental field of Vegetable Growing Department of The Russian State Agricultural University – Moscow Timiryazev Agricultural Academy. Studies were conducted from 2014 to 2019. Sowing the seeds was carried out in the 3rd decade of March in cassettes in a winter greenhouse. Seedlings planted in the field at the end of MayField experiments were laid at the «Vegetable Experimental Station named V.I. Edelstein » in accordance with generally accepted methods of field experiments. A comprehensive comparative assessment of the studied samples was carried out according to a number of criteria, in accordance with the recommendations of the State Register of Selection Achievements and the matrix of the morphological description of plants of the Lamiaceae family developed at the Leibniz-Institut for Pflanzengenetik und Kulturpflanzenforschung (IPK, Germany). Harvesting of raw materials and crop yield was carried out in the phase of mass flowering. Laboratory studies were carried out in the laboratories of the Vegetable Growing Department, Department of Botany, Selection and Seed Production of Garden Plants, Russian State Autonomous University – Moscow Agricultural Academy named after K.A. Timiryazev. The quantitative determination of essential oil was carried out according to the GF RF XIV. Statistical analysis was performed using Microsoft Excel.Results. The possibility of growing samples of Thymus vulgaris L. of different geographical origin under the conditions of introduction in the Moscow region is shown. A comparative study of the main morphological characteristics of plant samples of Thymus vulgaris L. revealed significant variability in the form of inflorescence, leaf index, the presence or absence of pubescence, anthocyanin staining, torsion of the leaf, color of corollas and leaves, plant height, yield, quantitative content of essential oil and flavonoids. At the same time, the height of the plants was relatively stable every year and between varieties. According to a set of indicators, the most productive and stable samples was “Di Roma”, which is characterized by a high yield of aerial mass (104 g / plant), a consistently high content of essential oil (1.04-1.8%) with a predominant thymol component (39-80%), high flavonoid content (1,47-2,26%). Varieties "Medoc" and "Deutsche Winter", which at a lower yield are characterized by a high content of essential oil and flavonoids.